Global trends in digital transformation and media positioning of universities in social networks - O. N. Tomyuk; A. V. Diachkova; A. N. Novgorodtseva (Цифровая социология, 2022)
For modern universities, social media is a competitive environment and a platform to increase their brand awareness in global and national rankings and promote educational, scientiﬁc and innovative services to a social media audience using marketing tools. The positioning of a modern university in social media is an activity focused on presenting the university and its services in the most advantageous way, popularising science. The aim of the study is to examine global trends in the positioning and digital transformation of university media activity in social media based on open statistical data. The authors analysed university presence indices in eight social networks (VK, Instagram, Facebook, YouTube, Telegram, Twitter, OK, Tik-Tok) of universities from the top 10 media activity rankings (2021), taking into account the speciﬁcs of each social network. The universities with the maximum media presence in each social network are highlighted. It is noted that a prominent presence on social media is based on working on the university’s positive media image and implementing global media positioning trends into strategic development. Two different strategies for positioning in the media space have been detected, and social networks with great potential for positioning higher education institutions in terms of age and the market segment capacity they cover are noted. The study can be useful to sociologists, economists, marketing experts and university professors.